2018
DOI: 10.1186/s12896-018-0418-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of Escherichia coli to improve L-phenylalanine production

Abstract: BackgroundL-phenylalanine (L-Phe) is an essential amino acid for mammals and applications expand into human health and nutritional products. In this study, a system level engineering was conducted to enhance L-Phe biosynthesis in Escherichia coli.ResultsWe inactivated the PTS system and recruited glucose uptake via combinatorial modulation of galP and glk to increase PEP supply in the Xllp01 strain. In addition, the HTH domain of the transcription factor TyrR was engineered to decrease the repression on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 31 publications
2
44
0
2
Order By: Relevance
“…23 W3110, such as replacing PTS with the GalP-Glk system, relieving feedback inhibition of aroF, pheA and tyrR, and overexpressing aroD, the L-Phe titer of the Xllp21 strain reached 72.9 g L −1 in a 5 L fermenter after 52-h cultivation. 37 L-Phe production by C. glutamicum also has been widely reported. Through combinational expression of the key genes of the L-Phe biosynthesis pathway, modifying the glucose and L-Phe transport systems and blocking the acetate and lactate biosynthesis pathways, the titer of L-Phe reached 15.76 g L −1 under fed-batch fermentation conditions.…”
Section: Production Of Dhs Derivativesmentioning
confidence: 95%
“…23 W3110, such as replacing PTS with the GalP-Glk system, relieving feedback inhibition of aroF, pheA and tyrR, and overexpressing aroD, the L-Phe titer of the Xllp21 strain reached 72.9 g L −1 in a 5 L fermenter after 52-h cultivation. 37 L-Phe production by C. glutamicum also has been widely reported. Through combinational expression of the key genes of the L-Phe biosynthesis pathway, modifying the glucose and L-Phe transport systems and blocking the acetate and lactate biosynthesis pathways, the titer of L-Phe reached 15.76 g L −1 under fed-batch fermentation conditions.…”
Section: Production Of Dhs Derivativesmentioning
confidence: 95%
“…Such a reaction has been previously described in an engineered E. coli strain producing isopropanol (69) and in acetone production in Clostridium acetobutylicum (70). In these strains, a CoAtransferase was involved in the conversion of acetoacetyl-CoA into acetoacetate, using butyrate or acetate as CoA acceptors (69,70). Such a reaction in B. abortus may explain why the bab2_0278-bab2_0282 ABC transport system is downregulated when the bab2_0213-bab2_0217 locus is overexpressed.…”
Section: Discussionmentioning
confidence: 72%
“…Instead, as a last step, we propose that the CoAtransferase family III enzyme (Bab2_0217) present in the bab2_0213-bab2_0217 locus may catalyze a reversible transfer of coenzyme A from CoA-thioesters to free acids ( Figure S8) (53,68), leading to the formation of ketones. Such a reaction has been previously described in an engineered E. coli strain producing isopropanol (69) and in acetone production in Clostridium acetobutylicum (70). In these strains, a CoAtransferase was involved in the conversion of acetoacetyl-CoA into acetoacetate, using butyrate or acetate as CoA acceptors (69,70).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, there has been great interest in using PAL in clinical, industrial and biotechnological applications, because it contains a radical‐generating cofactor 4‐methylidene‐imidazole‐5‐one (MIO) . All studies have shown that l ‐phe can be produced with a high yield from glucose in a fermentation system, but the concentration of t ‐CA has proven too low by the fermentation of sugars (Table ) . Vargas‐Tah et al produced 530 μmol L –1 t ‐CA with the PAL enzyme from Arabidopsis thaliana .…”
Section: Introductionmentioning
confidence: 99%